Effects of allisartan, a new AT1 receptor blocker, on blood pressure and end-organ damage in hypertensive animals - Wu Ming-yue; Ma Xiu-juan; Yang Chu; Tao Xia; Liu Ai-jun; Su Ding-feng; Liu Jian-guo (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of allisartan, a new angiotensin II type 1 (AT1) receptor antagonist, on blood pressure (BP) and end-organ damage (EOD) in hypertensive rats and dogs. Methods: First, a single dose of allisartan was given intragastrically to evaluate the BP reduction in spontaneously hypertensive rats (SHRs), two kidney-one clip (2K1C) renovascular hypertensive rats and dogs, and Beagle dogs with angiotensin II-induced hypertension. Second, allisartan was mixed in rat chow for long-term treatment. After 4 months of drug administration, rats were instrumented to determine BP and baroreflex sensitivity (BRS). Observation of morphologic changes was used to estimate EOD. Third, the acute toxicity of allisartan was compared with that of losartan in mice. Results: BP was significantly decreased after intragastric administration of allisartan in SHRs, 2K1C rats, 2K1C dogs and Beagle dogs with angiotensin II-induced hypertension. Compared with the control, SHRs that received long-term treatment with allisartan exhibited an improved BRS and organ protective effects. Mice who were administered allisartan experienced less acute toxicity than those treated with losartan. Conclusion: Allisartan is highly effective for BP reduction and organ protection with low toxicity.